2012
DOI: 10.1007/s00227-012-1898-5
|View full text |Cite
|
Sign up to set email alerts
|

Field identification of ‘types’ A and B of the ascidian Ciona intestinalis in a region of sympatry

Abstract: The ascidian species Ciona intestinalis is a major model chordate in developmental and evolutionary biology, and an important fouling organism and invasive species. However, genomic investigation has recently revealed the existence of two cryptic species, genetically distinct yet without obvious morphological diVerences, currently referred to as types A and B. Here, we show that they are externally distinctive in a zone of sympatry in the western English Channel. Examining genotyped specimens, we found that ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(116 citation statements)
references
References 23 publications
(34 reference statements)
6
109
1
Order By: Relevance
“…The nominal species C. intestinalis (Linnaeus 1767) covers a complex of four cryptic species (Zhan et al 2010). Two of them, C. intestinalis species A and C. intestinalis species B (hereafter referred to species A and species B, respectively) are now considered pseudo-cryptic species since the advent of morphological criteria to distinguish them (Sato et al 2012). In addition, very recently, Brunetti et al (2015) showed that species A displays morphological features specific to the formerly described Japanese species Ciona robusta (Hoshino and Tokioka 1967), later synonymized under C. intestinalis, whereas species B fits with the C. intestinalis description by Millar (1953).…”
Section: Introductionmentioning
confidence: 98%
“…The nominal species C. intestinalis (Linnaeus 1767) covers a complex of four cryptic species (Zhan et al 2010). Two of them, C. intestinalis species A and C. intestinalis species B (hereafter referred to species A and species B, respectively) are now considered pseudo-cryptic species since the advent of morphological criteria to distinguish them (Sato et al 2012). In addition, very recently, Brunetti et al (2015) showed that species A displays morphological features specific to the formerly described Japanese species Ciona robusta (Hoshino and Tokioka 1967), later synonymized under C. intestinalis, whereas species B fits with the C. intestinalis description by Millar (1953).…”
Section: Introductionmentioning
confidence: 98%
“…The type A has also been designate as C. robusta [55] geographically distributed in the Mediterranean, Pacific, and Southern Atlantic coasts of Europe [54,56]. Nonetheless, evidence of incomplete reproductive isolation from the wild population within the shared range of A and B types, raises the taxonomic issue [57].…”
Section: Animalsmentioning
confidence: 99%
“…After removing duplicate records and a few records that presented obvious errors of georeference, the final dataset consisted of 776 from Northern Europe (considered here as the native range) as well as 107 presences registered in Canada, 98 records from the Pacific coast of the United States, 212 from Southern Europe, and 24 records from Japan. Due to their morphological similarity, and the consequent difficulty that involves the identification of each species in the field (but see Sato et al, 2012), we cannot unambiguously attribute to neither of the species of the genetic complex the records that are available at the public database. Therefore, we decided to follow Zhan et al, (2010) and allocate the set of occurrences to the species that dominates a specific area.…”
Section: Species Occurrence Datamentioning
confidence: 99%